The Mystery in the Eye of the Beholder: An Analysis of the Gaze and Power in Martin Amis’ London Fields and Night Train. - Güneş, Mustafa (Journal of History Culture and Art Research, 2021)
Amis’s novels dating the 80s and 90s and portraying mostly the lives of the modern English, more specifically the Londoner, are provocative for the way they represent women. They are sometimes classified as the “ladlit” or at times dismissed all together out of the canon because they confine women mostly in patriarchal cliché female figures, or silence them to an extent that would discard the very existence of women in these texts. Among these ladlits, London Fields strikes the reader at first glance as the ladlit par excellence; yet, the protagonist in the novel is an extraordinary woman, Nicola Six, and her representation in the novel is exceptional in Amis’s oeuvre. When this novel is read in relation to another woman-starring Amisian novel, Night Train (1997) which features a hardboiled female detective, the result would be thought-provoking for gender studies across Amis’s works. Therefore, in what follows, the way Amis portrays Nicola Six is studied together with another fictional female figure, Mike Hoolihan of the novel Night Train, and the focus of the study is limited to the analysis of the characterization of the protagonists in relation to the concepts of “seeing” and “being seen” together with such mediums of power and the ideology as “the authority” “the author,” and “the reality.”